Alteration in the Cytokine Secretion of Bone Marrow Stromal Cells from Patients with Chronic Myelomonocytic Leukemia Contribute to Impaired Hematopoietic Supportive Activity - Hui Shi; Yingshao Wang; Rong Li; Wen Xing; Feng-Chun Yang; Jie Bai; Yuan Zhou (Hindawi Limited, 2018)
Bone marrow stromal cells (BMSCs) represent an important cellular component of the bone marrow microenvironment, which play an important role in supporting and regulating the proliferation and differentiation of hematopoietic stem/progenitor cells (HSPCs). We have previously reported that the ability of BMSCs derived from CMML patients (CMML-BMSCs) in supporting the expansion of cord blood (CB) CD34+ cells was significantly reduced compared to BMSCs derived from healthy donors (HD-BMSCs). In addition, CMML-BMSCs led to a skewed differentiation of CB CD34+ cells favoring myeloid lineage compared with HD-BMSCs. To assess whether the altered cytokine secretion was one of the mechanisms to mediate the impaired hematopoietic supportive activity of CMML-BMSCs, a transwell coculture followed by cytokine array was performed. We showed that noncontacted coculture with CMML-BMSCs preferentially promoted the differentiation of CB CD34+ cells toward myeloid lineage. The expression levels of multiple cytokines (IL-6, IL-8, and GRO-β) were markedly reduced in CMML-BMSCs compared with HD-BMSCs. By supplementing IL-6, IL-8, or GRO-β, the hematopoietic supportive activity of CMML-BMSCs was partially restored. These results suggested that BMSCs may contribute to the pathogenesis of CMML by altering their cytokine secretion, which will shed light on the further investigation to develop novel therapeutic strategies for CMML patients.